THE EFFECT OF CREDIT RISK MANAGEMENT, MARKET RISK, LIQUIDITY RISK ON THE FINANCIAL PERFORMANCE OF STATE-OWNED BUSINESS ENTITIES - Sunaryo, Deni (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of credit risk management, market risk and liquidity risk on the financial performance of banks listed on the IDX. The population in this study are state-owned banking companies until 2021 with an observation period of 8 years (2014-2021). Thus the total population is 32 (4 banking x 8 years). The analytical methods used in this research are descriptive statistical analysis, multiple linear analysis, and hypothesis testing. The data processing process uses the SPSS version 20 program. Based on the results of the study, it can be concluded that there is a significant influence on credit risk and banking financial performance, there is a significant influence on market risk and banking financial performance, there is a significant influence on liquidity risk and banking financial performance., there is a significant influence between credit risk, market risk, liquidity risk and banking financial performance. Future researchers are expected to conduct further research on the variables of NPL, NIM, and LDR on banking financial performance in a focused manner by increasing the number of samples and extending the research period. So as to be able to provide an overview of the condition of the financial performance of the banking sector more broadly. Further research is expected to expand the object of research, namely not only state-owned banks, but all banks in Indonesia so that research results are better because of the higher element of data representation compared to taking fewer samples.